The Issuance of Building Use Rights Certificates in Water Areas (A Case Study of Kohod Village) - Muhammad Amin Rifai; Yulia Qamariyanti (CV. Ulil Albab Corp, 2026)
This research aims to examine the feasibility of issuing Building Use Rights (HGB) Certificates in water areas and analyze the legal consequences of dispute resolutions between the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) and certificate holders. The research method employed is normative legal research. The research findings indicate, first, that there are differing legal perspectives regarding the issuance of HGB Certificates in water areas. The issuance of HGB Certificates in such areas is permissible provided that the certificates are granted to individuals who have established structures within the vicinity of the water areas. Second, regarding the legal consequences of dispute resolution by the Ministry of ATR/BPN, parties who perceive their rights to be infringed upon by such decisions may file a lawsuit. The legal repercussions of dispute resolution concerning the cancellation of HGB Certificates in water areas through the Administrative Court depend on the court's verdict. Should the Administrative Court grant the lawsuit and annul the cancellation of the HGB Certificates, the status of the HGB Certificates shall be reverted to the previous holder.